2021
DOI: 10.1111/jocn.16040
|View full text |Cite
|
Sign up to set email alerts
|

Children’s psychosocial and behavioural consequences during their siblings’ hospitalisation: A qualitative content analysis from caregivers’ perspectives

Abstract: Research has increasingly focused on psychosocial issues among siblings of children with paediatric cancer, and other chronic illnesses or disabilities, including neurological disorders and autism spectrum disorders (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…In hospital settings, siblings of admitted children are specifically at risk of unhealthy psychosocial conventions, such as internalizing distress ( 27 ). Further, siblings attempt to maintain their usual self, an essential element of children's optimal growth and development, while controlling for internalizing and externalizing complexities ( 5 ). However, siblings are largely absent from family-centered care and pediatric healthcare settings ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In hospital settings, siblings of admitted children are specifically at risk of unhealthy psychosocial conventions, such as internalizing distress ( 27 ). Further, siblings attempt to maintain their usual self, an essential element of children's optimal growth and development, while controlling for internalizing and externalizing complexities ( 5 ). However, siblings are largely absent from family-centered care and pediatric healthcare settings ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, siblings are often overlooked by clinical staff due to a lack of apparent features in hospital settings ( 22 ). To grasp admitted children's siblings' condition and promote appropriate support, healthcare professionals must communicate and build good collaborative relationships with their parents and other caregivers ( 5 ). It is challenging for medical professionals to build good relationships with parents for siblings' support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now understood that hospitalization in early childhood, chronic illness or a life-threatening illness or injury can be a negative experience that challenges crucial brain development and strains the family system, placing a child at risk of adverse and lasting effects on their brain development and ultimately on health and well-being [ 48 , 49 ]. The negative experience can include not just the illness or the injury, but also aspects of the hospitalization and treatments provided.…”
Section: Impact Of Hospitalization and Critical Illness On Child Healthmentioning
confidence: 99%
“…Even when they were not tandem feeding, many mothers described being split up from their other children as painful. The needs of siblings of hospitalised children have been previously reported, with many identified negative outcomes such as anxiety, becoming withdrawn, or taking on more adult responsibilities (Niinomi and Fukui, 2022). The impact on mothers of being separated from their other child or children while one is resident on the paediatric ward is less wellresearched, though some studies have found this to be one of the reported stressors (Hagstrom, 2017;Foster et al, 2019;Abela et al, 2020;Alzawad et al, 2022).…”
Section: Rq 1: What Is the Current Breastfeeding Training Provision A...mentioning
confidence: 99%